Nash equilibrium as an analytical tool for Public Administration: diagnosing pathologies and intervention strategies in the Greek context (European Journal of Government and Economics, 2026)
This article applies Game Theory to diagnose persistent pathologies in public administration, such as bureaucratic inertia, as stable sub-optimal Nash Equilibria. Through a systematic literature review focused on the Greek context, it proposes a conceptual shift for public administration from a passive 'player' to a proactive 'game designer' who strategically alters incentives, rules, and information. The analysis reveals that this framework provides a practical roadmap for addressing deep-seated issues like tax evasion and inter-agency conflict by transforming dysfunctional equilibria. Ultimately, it offers an actionable model for designing effective reforms that can move complex administrative systems from deadlock toward sustainable cooperation.